Guttman scaling in agoraphobia: cross-cultural replication and prediction of treatment response patterns. - Margraf, J; Ehlers, A; Taylor, C; Arnow, B; Roth, W (1990)
The Fear and Avoidance Scales (FAS) is an 11-item questionnaire consisting of two subscales that measure features of agoraphobia and claustrophobia and that were demonstrated to be valid Guttman scales in a British clinical population. The purposes of the study reported here were to replicate the scale characteristics in the United States and to determine if improvement during treatment would follow the sequence predicted by the hierarchy implied in the scales. The FAS was given to 25 female agoraphobics before and after behavioural treatment. A principal components analysis replicated the agoraphobia and claustrophobia factors established in the British sample. Scalogram analyses showed that the Claustrophobia subscale of the FAS was a valid Guttman scale in the US sample whereas the Agoraphobia subscale yielded a high coefficient of reproducibility but a low coefficient of scalability. Treatment reduced the patients' fears and avoidances in the predicted sequence since for both scales the hierarchy of items remained unchanged following treatment.